2020
DOI: 10.14419/ijet.v10i1.31255
|View full text |Cite
|
Sign up to set email alerts
|

Wood-steel composite shear walls with openings

Abstract: This paper reports an investigation into the behaviour of wood-steel composite shear walls, consisting of strand laminated lumber boundary frames with infill steel plates. Recently it has been shown that wood-steel composite shear wall systems can offer various advantages over code-approved wood frame shear walls, including architectural flexibility. However, further research is needed so as to gain a better insight and understanding into the structural behaviour of this lateral load resisting system. On this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…To capture the material's nonlinearity with accuracy, Hill's yield criterion (Hill, 1948;Hill, 1998) has been selected to describe the anisotropic plastic behaviour of the cross-laminated timber. The accuracy of Hill's model for capturing the non-linear behaviour and failure mode of timber has been previously investigated by (Xu et al, 2014;Vogiatzis et al, 2020).…”
Section: Timber Materials Modelmentioning
confidence: 99%
“…To capture the material's nonlinearity with accuracy, Hill's yield criterion (Hill, 1948;Hill, 1998) has been selected to describe the anisotropic plastic behaviour of the cross-laminated timber. The accuracy of Hill's model for capturing the non-linear behaviour and failure mode of timber has been previously investigated by (Xu et al, 2014;Vogiatzis et al, 2020).…”
Section: Timber Materials Modelmentioning
confidence: 99%
“…The type 2 wood steel composite shear wall system, WSCSW-T2, has been recently developed and validated by the authors (Figure 3) for computing the behaviour of tested specimens. The details of the generated 3D numerical models and their validation using experimental results are discussed in detail in [4]. These validated models were developed using the Finite Element Method (FEM) and provided further insight into the post-elastic behaviour of WSCSW-T2 systems.…”
Section: Objective and Approachmentioning
confidence: 99%
“…To capture the material's nonlinearity with accuracy, Hill's yield criterion (Hill, 1948;Hill, 1998) has been selected to describe the anisotropic plastic behaviour of the cross-laminated timber. The accuracy of Hill's model for capturing the non-linear behaviour and failure mode of timber has been previously investigated by (Xu et al, 2014;He et al, 2018;Vogiatzis et al, 2020).…”
Section: Timber Materials Modelmentioning
confidence: 99%
“…The numerical model could not be validated against experimental results since there is lack of available experimental data of the same hybrid system in the international literature. Therefore, the authors used as a guide a numerical model of a similar hybrid system that they had built in a recent study (Vogiatzis et al, 2020) which had been validated using experimental data found in (Conrad and Phillips, 2019). Material parameters and techniques used in that model were employed in the current numerical simulation to ensure the validity and accuracy of the model.…”
Section: Boundary Conditions Loading Procedures and Validationmentioning
confidence: 99%
See 1 more Smart Citation